SINTESIS HIDROKSIAPATIT DARI TULANG SAPI DENGAN METODE BASAH PADA BERBAGAI WAKTU PENGADUKAN DAN SUHU SINTERING - Reflin Yuliana; Erwin Abdul Rahim; Jaya Hardi (KOVALEN: Jurnal Riset Kimia, 2017)
Synthesis of hydroxyapatite (HAp) can be obtained from a reaction between calcium of cow bones and phosphate under wet method. Completely Random Design (CRD) was used in this research with three levels of stirring time and four levels of sintering temperature i.e. 60, 90, 120 minutes and 800oC, 850oC, 900oC, 950oC, respectively. The result showed that synthesis reaction at the sintering temperature of 850oC for 120 minutes were the best conditions to produce HAp. The yield of HAp product in those conditions was 48,5%. XRD spectrum of HAp had the highest intensity of 1000 at a 2Ɵ angel of 31.78o.Keywords: Hydroxyapatite, Stirring Time, Sintering Temperature, Cow Bone